1998
DOI: 10.1038/sj.ijo.0800633
|View full text |Cite
|
Sign up to set email alerts
|

Fat distribution and plasma lipid-lipoprotein concentrations in pre- and postmenopausal women

Abstract: OBJECTIVE: In the postmenopausal years, women develop a central pattern of fat distribution and an increased risk of developing cardiovascular disease (CVD). The possibility that these events are related has not been extensively investigated. The object of the present study was to test the hypotheses that, 1) menopause-related differences in lipids are associated with greater estimated intra-abdominal adiposity, and 2) the relationship between individual adipose depots and plasma lipids differs with menopausal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 35 publications
1
24
1
Order By: Relevance
“…In addition, many of these studies have controlled for more crude measures of adiposity, such as weight or BMI (14,16,29). Even though we ran the analyses with and without controlling for total fat and total lean tissue, which we have previously shown (30,31) to influence glucose and insulin dynamics, one could argue that excess weight or adiposity is the mechanism in which breastfeeding affects type 2 diabetes risk factors; this suggests that investigators should examine the effects that breastfeeding has on both obesity and type 2 diabetes risk factors with and without controlling for adiposity. In this study, breastfeeding was not associated with type 2 diabetes risk factors, as measured with OGTT or an FSIVGT test, with and without controlling for adiposity measures at baseline or across pubertal transitions.…”
Section: Results -mentioning
confidence: 99%
“…In addition, many of these studies have controlled for more crude measures of adiposity, such as weight or BMI (14,16,29). Even though we ran the analyses with and without controlling for total fat and total lean tissue, which we have previously shown (30,31) to influence glucose and insulin dynamics, one could argue that excess weight or adiposity is the mechanism in which breastfeeding affects type 2 diabetes risk factors; this suggests that investigators should examine the effects that breastfeeding has on both obesity and type 2 diabetes risk factors with and without controlling for adiposity. In this study, breastfeeding was not associated with type 2 diabetes risk factors, as measured with OGTT or an FSIVGT test, with and without controlling for adiposity measures at baseline or across pubertal transitions.…”
Section: Results -mentioning
confidence: 99%
“…He found that a predominance of fat in the upper body (android obesity) was associated with metabolic disturbances, while a predominance of fat in the lower body (gynoid obesity) was associated only with problems such as abdominal pressure and locomotor difficulty. Following menopause fat is increasingly deposited in the upper body region which is associated with low HDL-cholesterol, high apolipoprotein-B and high triglycerides 13 . Abdominal obesity has been linked to significant metabolic abnormalities including insulin resistance, hyperinsulinaemia, and elevated TAG levels as well as increased incidence of hypertension, glucose intolerance and diabetes mellitus.…”
Section: Volume 13 Issue 2 May 2014mentioning
confidence: 99%
“…8,9 Because oxidative stress modulates vascular smooth muscle cell (VSMC) tone, a key determinant of large artery compliance, 10,11 we hypothesized that oxidative stress may contribute to the reduced large artery compliance of estrogen-deficient postmenopausal women. Moreover, because abdominal adiposity and LDL cholesterol levels are elevated in postmenopausal women 12,13 and associated with oxidative stress, 14,15 we determined whether these factors were related to oxidative stresslinked suppression of large artery compliance.…”
mentioning
confidence: 99%